Education Methods to Improve Earthquake Preparedness Among Students: A Literature Review - Aan Nur'aeni; Salsabila Nabilla Puspa Ilham; Nara Raihani; Rini Dwi Puspitasari; Nurul Azmi Fauziyah; Myra D Oruga (Media Karya Kesehatan, 2023)
Earthquake is frequent disasters in Indonesia, and children or students are a group that is vulnerable to becoming victims. Preparedness is one of the efforts that can be made to anticipate losses due to disasters, one of which is through education. However, educational methods related to preparedness carried out for students are still little identified. This literature review aims to identify educational methods to improve earthquake disaster preparedness, especially for students. This study used a literature review with a descriptive review approach. The databases used include PubMed, ScienceDirect, DOAJ, Garuda, and Google Scholar, published from 2018 to 2022. The result of study that article selection was carried out, including checking for duplication, suitability of titles, abstracts, and inclusion and exclusion criteria. From this selection, 14 articles were included in this literature review. It was found that several methods can be used to improve disaster preparedness, such as the simulation method, education with lectures, singing, and others, as well as a combination of simulation with other methods, all of which can increase the preparedness score. Meanwhile, students who deal with a disaster have the potential to gain an increase in disaster preparedness. Simulation, education, and combining both methods were practical in increasing earthquake disaster preparedness. Keywords: Education, earthquake, preparedness, students.